2017
DOI: 10.1002/chem.201700954
|View full text |Cite
|
Sign up to set email alerts
|

Rigidly Tethered Bis‐phosphoric Acids: Generation of Tunable Chiral Fluorescent Frameworks and Unexpected Selectivity for the Detection of Ferric Ions

Abstract: We describe the straightforward synthesis of a series of bis-phosphoric acids (R,R)-1 a-d, featuring two chiral 1,1'-binaphthyl-phosphoric acid units that are tethered by rigid, π-conjugated linkers. The nature of the linker has a profound influence on the properties of the bis-phosphoric acids, such as their self-association behavior and their interaction with metal ions. This led to the identification of one preferred bis-phosphoric acid (R,R)-1 d, which shows selective fluorescence quenching in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…We recently reported a series of multidentate phosphoric acids ( 1 d / e / f , Figure 1 for 1 d / e / f ) that feature two or three BINOL‐based phosphoric acid diesters of the type (ArO) 2 P(O)OH. These systems were applied in organocatalysis, [13] but also for the chemosensing of metal‐ions [14] and amino acids [15] . By an acid‐catalyzed cyclization, we also generated the furane‐annelated phosphoric acid monoesters 11 d / e / f , which possess two or three binding units of the type (ArO)P(O)(OH) 2 .…”
Section: Figurementioning
confidence: 99%
“…We recently reported a series of multidentate phosphoric acids ( 1 d / e / f , Figure 1 for 1 d / e / f ) that feature two or three BINOL‐based phosphoric acid diesters of the type (ArO) 2 P(O)OH. These systems were applied in organocatalysis, [13] but also for the chemosensing of metal‐ions [14] and amino acids [15] . By an acid‐catalyzed cyclization, we also generated the furane‐annelated phosphoric acid monoesters 11 d / e / f , which possess two or three binding units of the type (ArO)P(O)(OH) 2 .…”
Section: Figurementioning
confidence: 99%
“…[46] Making use of the mechanical bond it is possible to impart al arge conformational flexibility,w hile generating al arge local concentration of catalyticallyactivephosphoric acid groups. [46] Making use of the mechanical bond it is possible to impart al arge conformational flexibility,w hile generating al arge local concentration of catalyticallyactivephosphoric acid groups.…”
Section: Scheme11 Calculated Transition States For the [4+ +2mentioning
confidence: 99%
“…Recently,o ur group has designed ac atenated bisphosphoric acid catalyst, in which am echanical bond is used to connect two binaphthyl-phosphoric acids. [46] Making use of the mechanical bond it is possible to impart al arge conformational flexibility,w hile generating al arge local concentration of catalyticallyactivephosphoric acid groups.…”
Section: Dual-site Substrate Bindingmentioning
confidence: 99%
“…Initial investigations showed that using only the sensors 1 a – f , the fluorescence responses were negligible for most amino acids, and only for those with nitrogen‐containing side‐chains (Lys, His, Arg, Trp) considerable fluorescence quenching was observed (Supporting Information, Figure S1). Based on our previous experience with the strong interaction of the bisphosphoric acids with metal ions, we turned to using metal salts in combination with the organophosphoric acids. We envisaged an initial metal‐induced fluorescence quenching, which would improve the differential response upon addition of the amino acids.…”
Section: Figurementioning
confidence: 99%